Kolaborasi Pentahelix dalam Pengembangan Pariwisata Berbasis Kearifan Lokal di Kabupaten Merauke - Edoardus E. Maturbongs; Ransta L. Lekatompessy (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Collaboration is the key word in building relationships among actors gathered in the development of tourism based on local wisdom. This study tries to describe and analyze the pentahelix model in the development of tourism based on local wisdom. Local Wisdom-based Tourism Development is the flagship program in changing the Merauke Regency Medium-Term Development Plan for 2016-2021. This research carried out by using the literature study (library research). Local wisdom-based tourism with collaboration between actors in the pentahelix model, supports to prioritize all forms of uniqueness that grow and develop in society, as well as providing agricultural values, which use both material and non-material.